Servant Leadership and Employee Performance: Joint Effects of Reward and Punishment Systems at Double R Garment, Denpasar, Bali - Ni Kadek Mirayani; Ni Made Dwi Puspitawati; Tiara Carina (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
In this era of globalization, employee performance is important for every organization to achieve its goals. Human resources are the most important asset for every organization; without human resources, the entire organizational system cannot run smoothly. High-quality human resources are a key factor for an organization, enabling employees to make a significant contribution to the success and growth of the organization. This study aims to examine the influence of servant leadership, rewards, and punishments on the performance of Double R Garment employees. The sample in this study consisted of all 35 employees of Double R Garment Denpasar. The research sample was saturated sampling. The data analysis technique used was regression analysis. The results of the study indicate that servant leadership and punishment simultaneously and partially have a significant effect on the performance of Double R Garment Denpasar employees.